Art vs. Science: In research and in the artistic experience field - Portugal, Pedro (2019)
The article discusses the relationship between art and science from the point of view of the artist as a researcher. A history of the relationship between artists and science is presented and three real examples are reported, in which the author conflicts and receives opposition from the scientific peers; Applicant to director of the Museum of Contemporary Art of Chiado, Lisbon; Gabinete da Polítécnica, Museum of Natural History and Science of Lisbon and sheep painting for the agricultural fair OVIBEJA, Beja.